Decision on Multiplier Grant to Ukraine: April 2023 - Global Partnership for Education (2023)
The Board of Directors approved a $25.55 million grant from the GPE Multiplier to Ukraine as accelerated financing.

Guidelines for Accelerated Funding - Global Partnership for Education (2023)
These guidelines describe the criteria for eligibility, amount, eligible activities and duration of accelerated funding from GPE.

Education in Ukraine - Global Partnership for Education (2022)
Learn more about Ukraine's education objectives and strategy, view grant information and education data, and explore the results and progress made.

Education in Ukraine: Over $51 million in grants and in-kind support announced from GPE, Google and Microsoft - Global Partnership for Education (2023)
As the war continues in Ukraine, severely disrupting education, GPE, Google, Microsoft Corporation and UNESCO will provide over US$51 million for distance learning and psychosocial support for children in conflict-affected areas. The program will be rolled out by UNESCO and UNICEF in Ukraine in partnership with the Ministry of Education and Science of Ukraine.

Ukraine: Education brings mental health support to children - Global Partnership for Education (2025)
Read how GPE and partners are helping increase the capacity of Ukraine’s educators to provide children with mental health services.

Accelerated Funding Grant Progress Report - Global Partnership for Education (2023)

Approval of Multiplier Grant to Ukraine as Accelerated Funding - Global Partnership for Education (2023)

Guidelines: System Capacity Grant - Global Partnership for Education (2024)

Achieving gender equality in and through education - Global Partnership for Education (2019)

Education in Sierra Leone | Where We Work | Global Partnership for Education - Global Partnership for Education (2007)
Learn more about education in Sierra Leone, view grant information and education data, and explore the results and progress made by the country.

GPE's Engagement on Domestic Financing for Education - Global Partnership for Education (2018)

Education in Madagascar - Global Partnership for Education (2020)
See education data for Madagascar and learn about GPE programs, grants, results and progress.

Senegal - Global Partnership for Education

Education in Tanzania - Global Partnership for Education (2020)

Pakistan (Balochistan): Using technology to bring education to the most remote areas - Global Partnership for Education (2019)

Education in Yemen - Global Partnership for Education (2020)
See education data for Yemen and learn about GPE programs, grants, results and progress.

Programa de Educação em Emergência 2020-2021 financiado pela Parceria Global da Educação - Global Partnership for Education (2020)

Proposal for GPE Accelerated Funding for COVID-19 Response (Malawi) - Global Partnership for Education (2020)

Zambia COVID-19 Accelerated Funding Application Form - Global Partnership for Education (2020)

Global Partnership for Education provides $68 million in grants for education response to COVID-19 (coronavirus) - Global Partnership for Education (2020)

Grant request to finance Rwanda COVID-19 education response from COVID-19 accelerated funding window under the GPE fund - Global Partnership for Education (2020)

Ghana COVID-19 Accelerated Funding Application Form - Global Partnership for Education (2020)

3 examples of mother tongue education to improve learning | Blog | Global Partnership for Education - Global Partnership for Education (Education for All blog, 2019)
GPE supports mother tongue education as a key component of the foundation of learning. On International Mother Tongue Day we review how three partner countries—Eritrea, The Gambia and Uzbekistan—with help from GPE, are implementing mother tongue programs.

Cover Note for COVID-19 Accelerated Funding Request - Global Partnership for Education (2020)

Sierra Leone: The power of great teaching in times of crisis | Stories of change - Global Partnership for Education
The Ebola crisis that plagued Sierra Leone in 2014-2016 had an unexpected positive consequence: giving learners access to the country’s best teachers through an innovative radio educational program. This experience served the country well when the COVID-19 pandemic hit.

KENYA GPE COVID 19 Learning Continuity in Basic Education Project - Global Partnership for Education (2020)

Global Partnership for Education - Global Partnership for Education (2021)

Global Partnership for Education launches new public-private initiative to address the data challenge in global education - Global Partnership for Education (Global Partnership for Education, 2018)
In an effort to help developing countries strengthen their collection, management and utilization of education data, high-level representatives from the private sector, international organizations, developing country governments and other partners are coming together at the Global Partnership for Education (GPE) Financing Conference to launch a major new initiative called the Education Data Solutions Roundtable.

Education in Pakistan - Global Partnership for Education (Global Partnership for Education, 2021)
See education data for Pakistan and learn about GPE programs, grants, results and progress.

Cover note for COVID-19 accelerated funding request - Global Partnership for Education (Global Partnership for Education, 2020)

Education in Tanzania - Global Partnership for Education (Global Partnership for Education website, 2021)
See education data for Tanzania and learn about GPE programs, grants, results and progress.

Using technology to bring education to the most remote areas - Global Partnership for Education (2019)

Application and program document for COVID-19 accelerated funding for Kenya - Global Partnership for Education (2020)

Kenya Partnership Compact. 2021 | Documents | Global Partnership for Education - Global Partnership for Education (2021)

Data Must Speak about Positive Deviance Approaches to Learning - Global Partnership for Education (GPEKIX)
Keywords: ⛔ No INSPIRE recid found

Cover Note for Lao PDR COVID-19 Accelerated Funding Request - Global Partnership for Education (Global Partnership for Education, 2020)

GPE 2025 Results Framework for Lao PDR - Global Partnership for Education (2023)
Keywords: ⛔ No INSPIRE recid found

Coordinated Action to Transform Education: What's in it for ministries of education - Global Partnership for Education (2023)
By leading and working through coordination bodies, ministries of education can mobilize smarter partnerships, ensure continued commitments to collective action and generate evidence for policy making, learning and adaptation.

Guidelines for Education Sector Plan Preparation - Global Partnership for Education (GPE) (2015)

Education sector analysis methodological guidelines - UNESCO-IIEP; World Bank; UNICEF; Global Partnership for Education (2014)
The Methodological Guidelines provide methods for carrying out a comprehensive analysis of the education sector in developing countries. Volume 1 of the guidelines discusses the context for the development of the education sector, enrollment, internal efficiency, out-of-school children, cost and financing, quality, system capacity and management, external efficiency and equity.

Education sector analysis methodological guidelines. Vol. 2: Sub-sector specific analysis - UNESCO-IIEP; World Bank; UNICEF; Global Partnership for Education (2019)
The purpose of these guidelines is to provide methods for comprehensive education sector analyses to support the preparation and monitoring of education sector plans. They are an update of a 1999 document that has been used to support the preparation of approximately 70 Education Country Status Reports (CSR) in more than 40 countries. The goal of the guidelines is to strengthen national capacities in order that Government teams can conduct education sector analyses with progressively less external support.